2015
DOI: 10.1108/jcp-06-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

A model for differentiating school shooters characteristics

Abstract: Purpose – The purpose of this paper is to explore the potential for developing a model for differentiating school shooters based on their characteristics (or risk factors) before the attack took place. Design/methodology/approach – Data on 40 school shootings was compiled from the National School Safety Center’s Report on School Associated Violent Deaths and media accounts. Content analysis of the cases produced a set of 18 variables rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
0
29
0
2
Order By: Relevance
“…However, it has been reported (Youngs, Ioannou, & Eagles, ) that specialisation is represented through expressive and instrumental offenders, although if this relates to geo‐behaviour remains unclear. It would be useful to examine the criminal narratives of these two groups of offenders as has been successfully applied in other studies (Ioannou, Canter, Youngs, & Synnott, ; Ioannou, Canter, & Youngs, ; Ioannou, Hammond, & Simpson, ; Ioannou, Synnott, Lowe, & Tzani‐Pepelasi, ; Ioannou, Synnott, Reynolds, & Pearson, ; Yaneva, Ioannou, Hammond, & Synnott, ). This would be in respect to their geographic profiles to ascertain if the lack of variation is geographic behaviour is consistent in their offender narrative.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported (Youngs, Ioannou, & Eagles, ) that specialisation is represented through expressive and instrumental offenders, although if this relates to geo‐behaviour remains unclear. It would be useful to examine the criminal narratives of these two groups of offenders as has been successfully applied in other studies (Ioannou, Canter, Youngs, & Synnott, ; Ioannou, Canter, & Youngs, ; Ioannou, Hammond, & Simpson, ; Ioannou, Synnott, Lowe, & Tzani‐Pepelasi, ; Ioannou, Synnott, Reynolds, & Pearson, ; Yaneva, Ioannou, Hammond, & Synnott, ). This would be in respect to their geographic profiles to ascertain if the lack of variation is geographic behaviour is consistent in their offender narrative.…”
Section: Discussionmentioning
confidence: 99%
“…If they are; then these items would be represented in similar regions and would provide evidence for distinct criminal narrative experiences in PD and psychopathic offenders. A number of studies from have found such MDS models to be productive in recent years (Ioannou, Canter, Youngs & Synnott 2015;Ioannou, Hammond & Simpson, 2015;Youngs, Ioannou & Eagles, 2016;Ioannou, Canter & Youngs, 2017;Ioannou, Synnott, Lowe & Tzani-Pepelasi, 2018;Yaneva, Ioannou, Hammond & Synnott, 2018, Synnott, Ioannou, Coyne & Hemingway, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study's large sample allows for the findings to be confidently accepted as a reliable representation of potential witnesses. The researchers acknowledge the significance of narrative theory within Investigative Psychology research (see Ioannou, 2006;Ioannou, Canter, Youngs, & Synnott, 2015;Ioannou, Hammond & Simpson 2015;Ioannou, Synnott, Lowe, & Tzani-Pepelasi, 2018;Ioannou, Synnott, Reynolds & Pearson, 2018). Thus, the authors propose that a fruitful direction for future research, in relation to the current journal's scope, would be to explore whether the personal narratives that eyewitnesses apply to their roles can influence the nature of their statements.…”
Section: Limitationsmentioning
confidence: 99%